Chapter Immagini della Russia tra Oriente e Occidente nel XVI secolo: politica, religione, culture nella Moscovia di Antonio Possevino - MELANI, IGOR (Biblioteca di Studi Slavistici, 2017)
This paper focuses on the analysis of Moscovia, written by Antonio Possevino soon after his diplomatic mission (1581-1582) to the Tsar Ivan IV. The text, composed as a geographical and ethnographical description of a given territory, became a collection of theological and controversial writings on the topic of the eastern Greek and Muscovite schism during its 40 years of editorial history. A deeper analysis of some political aspects of the text, though, shows how these different parameters were somehow inextricably connected within the catholic vision of the 'orthodox' East.